2016
DOI: 10.3892/ijo.2016.3605
|View full text |Cite
|
Sign up to set email alerts
|

Silencing Aurora-A with siRNA inhibits cell proliferation in human lung adenocarcinoma cells

Abstract: Aurora kinase A (AURKA) is an oncogenic serine/threonine kinase, it plays important roles in tumorigenesis and chemoresistance. In this study, we investigated the expression of AURKA in lung adenocarcinoma tissues, the role of small interference RNA targeting AURKA on growth, cell cycle, and apoptosis of lung adenocarcinoma cell lines in vitro. The AURKA is highly expressed in lung adenocarcinoma tissues and human lung adenocarcinoma cell lines. Lentivirus-mediated short hairpin RNA (shRNA) was used to knock d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Cell-division cycle protein 20 interacts with cadherin-1 to regulate anaphase-promoting complex and cyclin-dependent kinases during cell cycle. Dysregulation of Aurora kinase A has been associated with cancers of the lung, 30 prostate, 31 and breast. 32 We have performed oral gavage using human stool in this experiment.…”
Section: Basic and Translational Atmentioning
confidence: 99%
“…Cell-division cycle protein 20 interacts with cadherin-1 to regulate anaphase-promoting complex and cyclin-dependent kinases during cell cycle. Dysregulation of Aurora kinase A has been associated with cancers of the lung, 30 prostate, 31 and breast. 32 We have performed oral gavage using human stool in this experiment.…”
Section: Basic and Translational Atmentioning
confidence: 99%
“…[ 32 , 36 , 37 ] Knockdown of AURKA and FEN1 inhibit the migration, invasion, and proliferation of LUAD cells and induce apoptosis. [ 38 , 39 ] More importantly, AURKA is a driving force for the evolution of resistance to third-generation EGFR inhibitors in LUAD and associated with epithelial mesenchymal transition. [ 40 ] Recently, it is found that the deregulation of transcriptional levels and posttranscriptional modification of GAPDH, which is traditionally considered as a critical enzyme of glycolytic process, is an important determinant for tumor cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…Among these 10 candidates, six have been reported as Lung cancer‐related genes. It has been discovered AURKA was highly expressed in LUAD and played important roles in the cell cycle and apoptosis of human LUAD cells . Chen et al unraveled HMGA1, a NF‐κB signaling related factor, can be regulated by miR‐26 and associated with prognosis of LUAD patients.…”
Section: Discussionmentioning
confidence: 99%